Analisis Pemberdayaan Perempuan Desa (Studi di Desa Bulutengger Kecamatan Sekaran Kabupaten Lamongan) - Weni Rosdiana (Universitas Muhammadiyah Sidoarjo, 2015)
The purpose of this study described the empowerment in terms of empowerment dimensions and form of women empowerment in the Bulutengger village. This type of research was qualitative descriptive. The results of this study showed that the dimensions of the women empowerment in the Bulutengger village consists of women's welfare dimension, participation dimension, access dimensions, critical awareness dimensions and control dimensions. In addition, the form of women's empowerment in the Bulutengger village on empowering social aspects included regular activities of the fostering family welfare, gathering and recitation. Political aspects showed that lack of rural women empowerment. It is caused rural women have not been involved in decision-making at the village level. Empowerment of women in the psychological aspects are lacking because rural women still lack the motivation to improve confidence in arguing in a public forum/village.